HUBUNGAN AKREDITASI PUSKESMAS DENGAN KEPUASAN PASIEN DI PUSKESMAS KABUPATEN BANYUMAS - Eka Nofia Ningrum; Etlida wati (Universitas Fort De Kock, 2020)
Community Health Center (Puskesmas) must be periodically accredited at least once in three years. Accreditation status of Community Health Center (Puskesmas) can be affected by the availability and the completeness of health supply, facilities and infrastructure that support the health service itself. The purpose of this research to find out the correlation between the accreditation status of Community Health Center and the satisfaction of patients visiting Community Health Center in Banyumas Regency.The research method used this was a quantitative research that used analytical survey design with cross sectional method. implemented at 4 Community Health Centers with different accreditation The cluster sampling technique used purposive sampling while the data were collected using questionnaire, and analyzed using Chi square test. Research result There were 61 respondents at the age of 17-25, 135 respondents were female, 116 respondents were SMA/SMK/MAN graduates, and 99 respondents were self employed. The result of chi-square test was p-value0.023 ( 0.05). Conclusion there was correlation between the accreditation status of Community Health Center and the satisfaction of patients visiting Community Health Center in Banyumas Regency.